Determination of the mass fraction of granular mixture components by means of computer image analysis - Zapotoczny, Piotr (Technical Sciences, 2025)
The objective of this study was to determine the statistical relationship among density, volume, mass, and selected geometric parameters of rice grains. A gas pycnometer was employed for grain volume measurement, while a flatbed scanner and specialized software were utilized for the determination of geometric features. Over 70 geometric parameters were identified. Among these, for whole grains, the most effective shape-describing coefficients were Rb, W5, Nv, and LminE, whereas for broken grains, Lsz, LminE, Maver, and Uw proved to be superior. Correlation coefficients between density and geometric features ranged from 0.895 to 0.995 at a significance level of p<0.007. Based on these findings, it will be feasible to develop a grain quality assessment system utilizing 2D images and to infer the mass fraction of grains belonging to different quality grades